Market Reaction to Indonesia Golden Ring Award - Soejono, Fransiska (JDM (Jurnal Dinamika Manajemen), 2017)
This research is attended to analyze market reaction to announcement of Golden Ring Award period 2008-2015. Indonesia Golden Ring Award (IGRA) which was originally called as GRA is a form of award for the telecommunications industry in which the assessment team consist of the journalists who are daily covering the telecommunications industryÂ  It used an event study methodology to empirically evidence. The research samples are focused on 6 telecommunication firms listed in Indonesian Stock Exchange with judgement sampling technique. The secondary data consists of daily closing price of shares and composite stock price index with an estimation period during 21 days by using a market adjusted model. Hypotheses are tested by one sample t-test, paired t-test and independent sample t-test. There is significant market reaction to announcement of Golden Ring Award. The second Hypothesis also accepted i.e. there is a significance in different market reaction between the firms getting Golden Ring Award and the firms not getting Golden Ring Award, especially in best operator category. Whereas in best value added category, market didnâ€™t show significant reactions. This result gives implication related to the efficient capital market Hypothesis i.e. semi strong form efficiency are proven.